SIMULATION OF X-RAY DIFFRACTION PATTERN OF A VARIOUS KINDS OF NATURAL ZEOLITE CRYSTAL USING RIETAN PROGRAM - Supandi Suminta (Jurnal Zeolit Indonesia, 2003)
The simulation analysis of natural zeolite crystal structure have been carried out using RIETAN program. The simulation results provide diffraction pattern of some crystal structure data representing as zeolite materials. There are two sets of input data: First Global parameter: a. parameter to correct the zero-point shift of the diffraction pattern: zero-point error,Z, b. parameter to calculate the background: background parameters. Second: Phase-dependent parameters: a. parameter to adjust integrated intensities:scale factor,S, b. prefered orientation parameters, c. profile parameters:FWHM parameters,d parameters to determine peak position: lattice parameters and e.crystal structure parameters: fractional coordinates. The output data contain some information such as:profile diffraction pattern, R factor, final adjusted parameters and their estimated standard deviations, lattice parameters and unit cell volume, structure parameters, number and weight of each species in the unit cell and density,and summary of reflection such as: hkl, 2 theta, d, observation intensity, calculated intensities and structure factors. These output data provide diffraction patterns for some zeolite phases, i.e.: clinoptilolite, heulandite, mordenite, analcime, phillipsite, chabazite and erionite. Results show that was significant and the application can be used for all kind of zeolites and other crystal materials in general applications. The program can be applied easily and the resulting patterns represent all phases significandly. RIETAN simulation program is expected to help hope that helpful suggestion for all people who are identification and characterisation of zeolites qualitatively.